The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1118/1.1287439
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of positron emission mammography for detection of breast cancer. A phantom study

Abstract: Positron emission mammography (PEM) is a new, specialized imaging modality utilizing PET radiopharmaceuticals to detect breast cancer. The capabilities and limitations of PEM in detecting breast tumors were investigated with a series of phantom experiments. The PEM imager was mounted on a standard Lorad biopsy table (separated by 18 cm). In the initial phase of the investigation, basic scanner parameters (resolution, sensitivity, and scatter fraction) were measured. The effects of a number of breast imaging pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 28 publications
0
39
0
Order By: Relevance
“…It brings together a favorable combination of high-density scintillator crystals coupled to compact photodetectors, arranged in a double readout scheme capable of providing depth-of-interaction (DOI) information [5]. Such characteristics could significantly improve breast imaging without sacrificing neither the sensitivity nor the spatial resolution of the system [6,7]. Experimental measurements has already demonstrated that Clear-PEM detector modules have adequate performance, achieving in particular a measurement of the photon interaction point along the crystal length with 2 mm FWHM resolution.…”
Section: The Clear-pem Scannermentioning
confidence: 99%
“…It brings together a favorable combination of high-density scintillator crystals coupled to compact photodetectors, arranged in a double readout scheme capable of providing depth-of-interaction (DOI) information [5]. Such characteristics could significantly improve breast imaging without sacrificing neither the sensitivity nor the spatial resolution of the system [6,7]. Experimental measurements has already demonstrated that Clear-PEM detector modules have adequate performance, achieving in particular a measurement of the photon interaction point along the crystal length with 2 mm FWHM resolution.…”
Section: The Clear-pem Scannermentioning
confidence: 99%
“…An increasing number of PET cameras optimized to image the breast have been proposed or constructed [1][2][3][4][5][6][7][8][9]. These cameras, commonly known as Positron Emission Mammography or PEM cameras, restrict the field of view to a single breast, and are expected to have higher performance and lower cost than a conventional PET camera.…”
Section: Introductionmentioning
confidence: 99%
“…The past several years have seen a number of designs for PET cameras optimized to image the breast [1][2][3][4][5][6][7][8][9], commonly known as Positron Emission Mammography or PEM cameras. The guiding principal behind PEM instrumentation is that a camera whose field of view is restricted to a single breast will have significantly higher performance and lower cost than a conventional PET camera.…”
Section: Introductionmentioning
confidence: 99%